THE IMPACT OF THE 7th BATCH TEACHING CAMPUS PROGRAM ON THE TRANSFORMATION OF THE LEARNING ENVIRONMENT AT TIKUNG ISLAMIC JUNIOR HIGH SCHOOL: IMPROVING LITERACY, NUMERACY, AND A QUALITY LEARNING ENVIRONMENT - Basannang, Siti Mariani; Irawan, Mohamad Rizal Nur; Maimunah, Handariyatul (Antis-publisher, 2024)
Objective: This study examines the impact of the 7th Batch Teaching Campus Program, part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, on enhancing literacy, numeracy, and the overall learning environment at Tikung Islamic Junior High School. Methods: Employing a combination of observation, discussion, and program implementation, university students collaborated with school staff to design activities such as literacy and numeracy games, interactive media, and teacher training. This structured work program, developed through the School Communication and Coordination Forum (FKKS), included activities like the Student Work Gallery, Visual Voyage, and a Mathematics Fair, aiming to foster creativity, critical thinking, and engagement among students. Results: The program significantly improved students' literacy and numeracy skills, fostered a more interactive and enjoyable learning environment, and equipped students with essential digital skills. Teachers also benefited from training, enhancing instructional effectiveness. Novelty: By integrating community-based teaching initiatives with structured school programs, this study offers an innovative model for school-university partnerships in underperforming educational settings, highlighting scalable strategies for sustained educational enhancement. Conclusion: The program demonstrates a sustainable and impactful approach to improving educational quality through collaborative efforts between university students and secondary schools, contributing to a holistic and inclusive learning experience.